Prevention of patient harm in endodontic clinical practice (Research, Society and Development, 2025)
Introduction: Patient safety is one of the fundamental pillars of healthcare and one of the critical points in dental services, in which the well-being and safety of the patient must be respected. Objective: To identify the most frequent incidents and adverse events in endodontic practice, as well as the main measures aimed at their prevention. Methodology: The research has a qualitative and descriptive approach, using the Delphi Technique, through consensus among experts. The participants were invited dental surgeons specializing in endodontics, who collaborated by filling out forms. Results: Several incidents resulting from multifactorial errors in endodontic practice were identified, including incorrect diagnosis, instrument fractures, and canal perforations. Among the adverse events reported, allergic reactions to medications, soft tissue injuries due to substance extravasation, and flare-ups stand out. For proper risk management, the strategies identified by the experts were organized into different dimensions: evidence-based clinical practice; continuing and lifelong education; information and communication; standards, routines, and Standard Operating Procedures; organization of work before, during, and after the procedure; and other preventive measures. The panel emphasized that the adoption of a culture of safety, combined with the systematization of clinical processes and organizational accountability, contributes significantly to risk reduction and improved quality of dental care. Conclusion: The implementation of structured risk management measures in endodontics is essential to ensure patient safety and promote an efficient and reliable care environment.